Psychosocial morbidity associated with bipolar disorder and borderline personality disorder in psychiatric out-patients: Comparative study. (October 2015) - Zimmerman, Mark; Ellison, William; Morgan, Theresa A.; Young, Diane; Chelminski, Iwona; Dalrymple, Kristy
Abstract : Background: The morbidity associated with bipolar disorder is, in part, responsible for repeated calls for improved detection and recognition. No such commentary exists for the improved detection of borderline personality disorder. Clinical experience suggests that it is as disabling as bipolar disorder, but no study has directly compared the two disorders. Aims: To compare the levels of psychosocial morbidity in patients with bipolar disorder and borderline personality disorder. Method: Patients were assessed with semi-structured interviews. We compared 307 patients with DSM-IV borderline personality disorder but without bipolar disorder and 236 patients with bipolar disorder but without borderline personality disorder. Results: The patients with borderline personality disorder less frequently were college graduates, were diagnosed with more comorbid disorders, more frequently had a history of substance use disorder, reported more suicidal ideation at the time of the evaluation, more frequently had attempted suicide, reported poorer social functioning and were rated lower on the Global Assessment of Functioning. There was no difference between the two patient groups in history of admission to psychiatric hospital or time missed from work during the past 5 years. Conclusions: The level of psychosocial morbidity associated with borderline personality disorder was as great as (or greater than) that experienced by patients with bipolar disorder. From a public health perspective, efforts to improve the detection and treatment of borderline personality disorder might be as important as efforts to improve the recognition and treatment of bipolar disorder.